The Role of Conservative Management of Modified Moderate Alvarado Score(4-7) in Acute Appendicitis - Nawshirwan Hassan AbdulKarim; Faruk Hassan Faraj (Diyala Journal of Medicine, 2020)
Background: Reginald Fitz described appendicitis  in 1886.1From then the term appendicitis has been used. Acute appendicitis is the  Commonest cause of abdominal surgical intervention with a  prevalence of nearly  1 in 7 people[2].It is related to  occasional mortality and  high morbidity. Regarding conservative management an initial non-operative management for acute appendicitis was tried  in the 1950s but was not accepted at that time[16] .Conservative management of acute appendicitis is safe and associated with reduced rate of operation ,complication and reduced costs of treatment[17-18]. Treatment include bowel rest, intravenous antibiotic with3rd generation Cephalosporine and Metronidazole .Datas show successful result in 90% of patients in whom appendicitis was confirmed by CT however 1/4 of patients may require surgical intervention within one year [19].